An Investigation on the Relationship between Market Orientation, Innovation, Competitive Advantage and Marketing Performance - Nuvriasari, Audita; Ririn Puspita Sari (International Business Education Journal, 2023)
MSMEs are the backbone of the economy in developing countries, including Indonesia. In order to support economic growth, it needs to be accompanied by encouraging MSMEs performance to be more optimal. Therefore, the purpose of this study is to examine the effect of market orientation, innovation and competitive advantage on the marketing performance of Batik MSMEs. The research location is in Yogyakarta, Indonesia with a total sample of 43 Batik MSMEs. Analysis using multiple regression and the results of hypothesis testing prove that: (1) market orientation has no significant effect on marketing performance, (2) innovation has a significant positive effect on marketing performance, and (3) competitive advantage has a significant positive effect on marketing performance. The findings of this study indicate that competitive advantage is the dominant factor influencing the marketing performance of Batik MSMEs. Accordingly, MSMEs should focus on developing their competitive advantage and innovation to improve the marketing performance.